MicroRNA Mediation of Endothelial Inflammatory Response to Smooth Muscle Cells and Its Inhibition by Atheroprotective Shear Stress. Issue 7 (27th March 2015) - Chen, Li-Jing; Chuang, Li; Huang, Yi-Hsuan; Zhou, Jing; Lim, Seh Hong; Lee, Chih-I; Lin, Wei-Wen; Lin, Ting-Er; Wang, Wei-Li; Chen, Linyi; Chien, Shu; Chiu, Jeng-Jiann
<x xml:space="preserve">Abstract</x> Rationale: In atherosclerotic lesions, synthetic smooth muscle cells (sSMCs) induce aberrant microRNA (miR) profiles in endothelial cells (ECs) under flow stagnation. Increase in shear stress induces favorable miR modulation to mitigate sSMC-induced inflammation. Objective: To address the role of miRs in sSMC-induced EC inflammation and its inhibition by shear stress. Methods and Results: Coculturing ECs with sSMCs under static condition causes initial increases of 4 anti-inflammatory miRs (146a/708/451/98) in ECs followed by decreases below basal levels at 7 days; the increases for miR-146a/708 peaked at 24 hours and those for miR-451/98 lasted for only 6 to 12 hours. Shear stress (12 dynes/cm2) to cocultured ECs for 24 hours augments these 4 miR expressions. In vivo, these 4 miRs are highly expressed in neointimal ECs in injured arteries under physiological levels of flow, but not expressed under flow stagnation. MiR-146a, miR-708, miR-451, and miR-98 target interleukin-1 receptor–associated kinase, inhibitor of nuclear factor–κB kinase subunit-γ, interleukin-6 receptor, and conserved helix-loop-helix ubiquitous kinase, respectively, to inhibit nuclear factor–κB signaling, which exerts negative feedback control on the biogenesis of these miRs. Nuclear factor-E2–related factor (Nrf)-2 is critical for shear-induction of miR-146a in cocultured ECs. Silencing either Nrf-2 or miR-146a led to increased neointima formation of injured rat carotid artery under physiological levels of flow. Overexpressing miR-146a inhibits neointima formation of rat or mouse carotid artery induced by injury or flow cessation. Conclusions: Nrf-2–mediated miR-146a expression is augmented by atheroprotective shear stress in ECs adjacent to sSMCs to inhibit neointima formation of injured arteries.